Health professional and patient interaction - Purtilo, Ruth B. (Elsevier, 2014)
Offers strategies for effectively communicating with patients of all ages, as well as abusive, depressed and impaired patients, are illustrated through examples and various scenarios. This book emphasizes respectful interactions in a wide range of health care settings